2009
DOI: 10.1186/1756-9966-28-118
|View full text |Cite
|
Sign up to set email alerts
|

Does vimentin help to delineate the so-called 'basal type breast cancer'?

Abstract: Background: Vimentin is one of the cytoplasmic intermediate filament proteins which are the major component of the cytoskeleton. In our study we checked the usefulness of vimentin expression in identifying cases of breast cancer with poorer prognosis, by adding vimentin to the immunopanel consisting of basal type cytokeratins, estrogen, progesterone, and HER2 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…[5] Eight of the patients with significant vimentin positivity were seen in females in their golden years (50 years) and one case in a 65 year old lady. An overall mean young age (45.6 years) has also been documented by Kusinska et al and Chen et al [11,17] Tumor grade is an important prognostic factor in carcinoma breast. The comparison of our findings with other studies is in Table 3.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…[5] Eight of the patients with significant vimentin positivity were seen in females in their golden years (50 years) and one case in a 65 year old lady. An overall mean young age (45.6 years) has also been documented by Kusinska et al and Chen et al [11,17] Tumor grade is an important prognostic factor in carcinoma breast. The comparison of our findings with other studies is in Table 3.…”
Section: Discussionmentioning
confidence: 57%
“…Vimentin expression in tumor cells has been reported to be 7.7%, 21.1%, 14%, and 13.4% by various authors. [5,[11][12][13] . Our finding was lesser than Thomas et al who noted positivity in 25/53 (47.1%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…7,[9][10][11] Similar correlations between vimentin overexpression and invasion are observed in cancer cell lines and mouse models across most tumor types. 6,12 In breast cancer, in particular, vimentin positive tumors were observed in younger women, usually lacked estrogen and progesterone receptors, and correlated with high-grade cancer 13 and tumor size. 14 Studies done in vitro show that vimentin is essential for cell motility and migration, loss of vimentin expression nearly eliminates cell migration 5,[15][16][17] and increased expression enhances migration.…”
mentioning
confidence: 99%
“…12,13 In the MCF-7 cells, vimentin gene transfection caused increased invasiveness. 13 A previous study demonstrated that invasive breast cancer cell lines expressed more vimentin, suggesting its important role in identifying cases with worse prognosis.…”
Section: -11mentioning
confidence: 99%
“…13 A previous study demonstrated that invasive breast cancer cell lines expressed more vimentin, suggesting its important role in identifying cases with worse prognosis. 12 Our study was aimed to investigate the effect of repeated exposure of endoxifen with or without β-estradiol to MCF-7 breast cancer cell line on cell viability, morphology and EMT progression through the analysis of vimentin mRNA expression.…”
Section: -11mentioning
confidence: 99%